Shalawat Albanjari: a Musical Uniqueness for Psychological Well-Being Improvement among Higher Education Students - Queen Rahmah Rizqi Zaidah (TSAQAFAH, 2019)
AbstractLevels of stress and mental health disorders of adulthood increased five times higher than the conditions experienced in the era of the great depression in 1938 ago. The triggers came from school and popular culture in everyday life. The symptoms of burnout were also found in some college students, for example at the University of Maulana Malik Ibrahim Malang. This problem greatly affects their psychological well-being (PWB) which can make other continuity psychological problems. Shalawat Albanjari activities which have been found in Ma’had Sunan Ampel al-Aly (MSAA) UIN Malang as an old tradition has some certain values that can be expressed in terms of PWB. This study is ethnographic qualitative research. Subjects in this study are some students who become the active players of Shalawat Albanjari. The results showed that Shalawat Albanjari contains some values: psychological values, education values, social values, and spiritual values. Moreover, PWB can be conceptualized as a state of “being calm and peaceful because of the remembrance of God”. Doing Shalawat Albanjari as a routine activity can indirectly improve the PWB of the players.Keywords: Shalawat Albanjari, Shalawat, Psychological Well-Being, Music, Higher Education Students.AbstrakTingkat stres dan gangguan kesehatan mental di masa dewasa meningkat lima kali lebih tinggi dari kondisi yang dialami saat era depresi hebat pada 1938 lalu. Pemicunya berasal dari sekolah dan budaya populer dalam kehidupan sehari-hari. Gejala-gejala burnout juga ditemukan pada beberapa pelajar Perguruan Tinggi, tidak menutup kemungkinan juga terjadi pada pengurus Ma’had Sunan Ampel al-Aly UIN Malang. Hal ini tentu sangat mempengaruhi kesejahteraan psikologis mereka (PWB). Adanya kegiatan Shalawat Albanjari di Ma’had Sunan Ampel Al-Aly (MSAA) UIN Malang sebagai tradisi lama memiliki beberapa nilai tertentu yang dapat diungkapkan dalam kaitannya dengan Psychological Well Being pelakunya. Penelitian ini adalah penelitian kualitatif etnografi. Dua mahasiswa yang menjadi pelaku aktif Shalawat Albanjari menjadi subjek dalam penelitian ini. Hasil penelitian menunjukkan bahwa Shalawat Albanjari mengandung beberapa nilai utama, yaitu: nilai psikologis, nilai pendidikan, nilai sosial, dan nilai spiritual. Selain itu, PWB dapat dikonseptualisasikan sebagai keadaan “menjadi tenang dan damai karena mengingat Allah”. Melakukan Shalawat Albanjari sebagai kegiatan rutin secara tidak langsung dapat meningkatkan PWB para pelakunya.Kata Kunci: Shalawat Albanjari, Shalawat, Kesejahteraan Psikologis, Musik, Pelajar Perguruan Tinggi.